Land Management Legacy Affects Abundance and Function of the acdS Gene in Wheat Root Associated Pseudomonads - Ruscoe, Heather L.; Taketani, Rodrigo G.; Clark, Ian M.; Lund, George; Hughes, David; Dodd, Ian C.; Hirsch, Penny R.; Mauchline, Tim H. (Frontiers in Microbiology, 2021)
Land management practices can vastly influence below ground plant traits due to chemical, physical and biological alteration of soil properties. Beneficial Pseudomonas spp. are agriculturally relevant bacteria with a plethora of plant growth promoting (PGP) qualities, including the potential to alter plant physiology by modulating plant produced ethylene via the action of the bacterial enzyme 1-Aminocyclopropane-1-carboxylate (ACC) deaminase (acdS). This study evaluated the impact of land management legacy on the selection and function of wheat root associated culturable pseudomonads isolates. Three distinct previous land uses prior to wheat culture (grassland, arable and bare fallow) were tested and culturable pseudomonad abundance, phylogeny (gyrB and acdS genes), function (ACC deaminase activity) and the co-selection of acdS with other PGP genes examined. The pseudomonad community could to some extent be discriminated based on previous land use. The isolates from rhizosphere and root compartments of wheat had a higher acdS gene frequency than the bulk soil, particularly in plants grown in soil from the bare fallow treatment which is known to have degraded soil properties such as low nutrient availability. Additionally, other genes of interest to agriculture encoding anti-fungal metabolites, siderophores and genes involved in nitrogen metabolism were highly positively associated with the presence of the acdS gene in the long-term arable treatment in the genomes of these isolates. In contrast, genes involved in antibiotic resistance and type VI secretion systems along with nitrogen cycling genes were highly positively correlated with the acdS gene in the bare fallow’s cultured pseudomonad. This highlights that the three land managements prior to wheat culture present different selection pressures that can shape culturable pseudomonad community structure and function either directly or indirectly via the influence of wheat roots.